MENGGAGAS STANDAR TERTENTU OTONOMI DAERAH MELALUI MAHKAMAH KONSTITUSI - La Ode Muhaimin; La Ode Ali Mustafa; Nasrin (Faculty of Law, Universitas Gadjah Mada, 2023)
Abstract In Indonesia, the implementation of regional autonomy has been inconsistent with the concept of sovereignty where the president is the head of government and an open legal policy. These arguments have been employed by each governing system to justify centralized programs. This causes regional autonomy to be immobilized and eliminated the aspirations of Indonesia’s founders who mandated effective regional autonomy implementation. As a result, the Constitutional Court must reach an agreement on a level of regional autonomy to prevent further centralization. This research is normative legal research with a statutory, historical, and conceptual approach. The concept of regional autonomy originates from the principles of residual power and Westphalian sovereignty. The Constitutional Court created some regional autonomy criteria to execute its function as a positive legislator with the main goal of supporting the President and the DPR in fulfilling their responsibilities as lawmakers who made a mistake devised and approved.Abstrak Pelaksanaan otonomi daerah di Indonesia acapkali tidak konsisten mulai era orde lama sampai era reformasi karena disokong oleh tiga faktor konsep kedaulatan dalam negara kesatuan, presiden sebagai kepala pemerintahan, dan open legal policy. Tiga faktor ini menjadi dalil setiap rezim pemerintahan dalam melegitimasi kebijakannya yang sentralisitik. Akhirnya otonomi daerah menjadi lumpuh dan menenggelamkan cita-cita para pendiri bangsa Indonesia. Maka dari itu, Mahkamah Konstitusi perlu menggagas standar tertentu otonomi daerah sebagai konsensus untuk mencegah sentralisasi kekuasaan terulang kembali. Penelitian ini adalah penelitian yuridis normatif dengan pendekatan perundang-undangan, pendekatan historis, dan pendekatan konseptual. Gagasan standar tertentu otonomi daerah mengalir dari prinsip residual power dan prinsip kedaulatan Whestphalian yang menjadi asal kedaulatan dalam negara kesatuan. Standar tertentu otonomi daerah yang digagas oleh Mahkamah Konstitusi adalah dalam rangka memainkan perannya sebagai “positive legislator” dengan peruntukan utama membantu menyempurnakan tugas Presiden dan DPR sebagai pembentuk UU yang khilaf yang sengaja dibentuk dan ditetapkan.